A educação patrimonial e o ensino de geografia: experiência nas escolas públicas da cidade de Santa Maria - RS - Liberalesso, Cibele Pase (2013)
The Heritage Education in teaching Geography enables formation of individuals able to know and understand the place and living space, thus instigating the preservation and valorization of the past and also the present. She is the thread to work questions related to heritage, especially in the school environment, awakening consciousness preservationist. In this sense, the objective was to understand how teachers of geography School Municipal Vicente Farencena, Elementary School Municipal Padre Nobrega, State School Olavo Bilac, State School Marieta D‟ambrósio, all of Santa Maria- RS, has been discussing cultural plurality proposed by PCN‟s. For this it was necessary to identify how the PCN‟s Geography of the third and fourth cycle of basic education to address cultural diversity ; analyze the geography textbooks used by teachers; investigate together teachers what kind of discussions concerning the cultural questions had been conducted in classroom and school and have understanding about, was important Heritage Education. To know the reality of teachers of municipal schools as state, what their aspirations and their difficulties. With this purpose, and this research was supported the qualitative approach, because estimated the knowledge and experience of teachers. In this obliquity search valuing the results, since conditioned the better understanding about how Heritage Education has been worked, which will contribute to maybe a future implantation of a project of heritage education in schools Santa Maria.